Mining RNA‐seq data reveals the massive regulon of GcvB small RNA and its physiological significance in maintaining amino acid homeostasis in Escherichia coli. Issue 1 (9th November 2021) - Miyakoshi, Masatoshi; Okayama, Haruna; Lejars, Maxence; Kanda, Takeshi; Tanaka, Yuki; Itaya, Kaori; Okuno, Miki; Itoh, Takehiko; Iwai, Noritaka; Wachi, Masaaki
Abstract: Bacterial small RNAs regulate the expression of multiple genes through imperfect base‐pairing with target mRNAs mediated by RNA chaperone proteins such as Hfq. GcvB is the master sRNA regulator of amino acid metabolism and transport in a wide range of Gram‐negative bacteria. Recently, independent RNA‐seq approaches identified a plethora of transcripts interacting with GcvB in Escherichia coli . In this study, the compilation of RIL‐seq, CLASH, and MAPS data sets allowed us to identify GcvB targets with high accuracy. We validated 21 new GcvB targets repressed at the posttranscriptional level, raising the number of direct targets to >50 genes in E. coli . Among its multiple seed sequences, GcvB utilizes either R1 or R3 to regulate most of these targets. Furthermore, we demonstrated that both R1 and R3 seed sequences are required to fully repress the expression of gdhA, cstA, and sucC genes. In contrast, the ilvLXGMEDA polycistronic mRNA is targeted by GcvB through at least four individual binding sites in the mRNA. Finally, we revealed that GcvB is involved in the susceptibility of peptidase‐deficient E. coli strain (Δpeps) to Ala‐Gln dipeptide by regulating both Dpp dipeptide importer and YdeE dipeptide exporter via R1 and R3 seed sequences, respectively. Abstract : GcvB is the master small RNA regulator of amino acid metabolism and transport. Through the compilation of RNA‐seq data sets, we validated 21 new GcvB targets, and the GcvB regulon now comprises 54 genes in  Escherichia coli . GcvB represses most targets via either R1 or R3 seed sequence, but both R1 and R3 are required to fully repress  gdhA . GcvB also regulates  ilvLXGMEDA  by binding to at least four individual sites in the mRNA.